The DAMPAK MENONTON FILM ANIMASI UPIN DAN IPIN TERHADAP KARAKTER GOTONG ROYONG PADA ANAK SMPN 1 KUTOREJO KECAMATAN KUTOREJO KABUPATEN MOJOKERTO - LAILA, EMI ZULFA; Setyowati, Raden Roro Nanik (Universitas Negeri Surabaya (Unesa), 2024)
The sophistication of technology and information today with easy access makes filtering messages and information to students very important. In this modern era, television is no longer a luxury for Indonesian people. Cartoon shows are one of the many programs presented on the screen or other mass media. Currently, the value of the mutual cooperation character at SMPN 1 Kutorejo is still relatively low. For that, from the many animated films, the Upin and Ipin film is one of the shows that can be taken meaning and used as an intermediary to shape the character of SMPN 1 Kutorejo students. The Upin and Ipin animated film has many moral messages and character values. The value that appears most often is the mutual cooperation character. The purpose of this study was to (1) determine the response of students to the film, and (2) the impact of watching the Upin and Ipin Animated Film on the mutual cooperation character of SMPN 1 Kutorejo students. This study uses a qualitative approach with a descriptive method. Data were collected through observation and in-depth interviews. The source of the study was grade VII students. The results of the study showed that grade VII students gave a good response and the impact of watching the Upin and Ipin Animated Film had gone well in terms of the four stages of Albert Bandura's social learning theory. The positive impacts are increased social awareness, a sense of responsibility for oneself and others, prosocial behavior, and strengthening family values.